A multi-channeled vortex beam switch with moiré metasurfaces. (17th December 2021) - Cui, Cheng; Liu, Zheng; Hu, Bin; Jiang, Yurong; Liu, Juan
Abstract: Tunable metasurface devices are considered to be an important link for metasurfaces to practical applications due to their functional diversity and high adaptability to application scenarios. Metasurfaces have unique value in the generation of vortex beams because they can realize light wavefronts of any shape. In recent years, several vortex beam generators using metasurfaces have been proposed. However, topological charge generally lacks tunability, which reduces the scope of their applications. Here, we propose an active tunable multi-channeled vortex beam switch based on a moiré structure composed of two cascaded dielectric metasurfaces. The simulation results show that when linearly polarized light with a wavelength of 810 nm is incident, the topological charge from −6 to +6 can be continuously generated by relatively rotating the two metasurfaces. Meanwhile, different topological charges are deflected to different spatial channels, realizing the function of multi-channeled signal transmission. We also study the efficiency and broadband performance of the structure. The proposed multi-channel separation method involving vortex beams that can actively tune topological charges paves the way for the compactness and functional diversity of devices in the fields of optical communications, biomedicine, and optoelectronics.